Identification of Leptospira spp serogroups in alpacas from the IVITA Research Centre (Marangani, Cusco) - Better, Yaquelyn (2018)
The aim of this study was to identify the Leptospira spp serogroups present in alpacas from the Maranganí Experimental Station of the IVITA Research Center in Cusco, Peru. Blood samples from 126 alpacas older than one year of age were collected and analyzed by the serological microagglutination test (MAT). Serovars of international reference of 21 pathogenic serogroups were used. Results showed that 42.9% (34.51- 51.7%) of alpacas were seropositive to nine pathogenic serogroups: Icterohaemorrhagiae (12.7%), Pomona (11.1%), Panama (11.1%), Hurstbridge (9.5%), Ranarum (5.6%), Ballum (1.6%), Cypnopteri (1.6), Djasiman (0.8%) and Hebdomadis (0.8%). Likewise, 2.4% (3/126) of coagglutinations were obtained.